Social and Intellectual Capital Effect on MSME Performance: Innovation as a Mediator and Managerial Ability as a Moderator - Yani, Ahmad; ., Japar; Yohana, Corry (Journal of Cultural Analysis and Social Change, 2025)
Micro, small, and medium enterprises (MSMEs) in Bekasi Regency and City, West Java, often face challenges in maintaining competitiveness and sustainable performance due to limited innovation and managerial capacity. This study aims to analyze the influence of social and intellectual capital on MSME performance, with innovation as a mediating variable and managerial ability as a moderating variable. A quantitative approach was employed with a sample of 204 MSME owners or managers, determined using the Slovin formula from a population of 209,714 MSMEs. The results show that social capital significantly increases innovation and MSME performance, while intellectual capital also positively affects both innovation and performance. However, managerial ability improves MSME performance directly but does not moderate the relationship between social capital and performance. The novelty of this study lies in identifying managerial ability as an independent factor rather than a moderating variable, emphasizing the central role of innovation as the key mechanism linking social and intellectual capital to MSME performance.